The effect of coconut sugar on blood glucose level in prediabetes patients - Nurun Laasara; Yusniarita; Sari Lutfijah; Vira Zahra Alkharis; Siti Fatimah Sa’at (Alma Ata University Press, 2026)
Background: Diabetes not only causes premature deaths worldwide. This disease is also a major cause of blindness, heart disease and kidney failure. Prevention and control of diabetes mellitus in Indonesia is carried out so that healthy individuals remain healthy and people who already have risk factors can control them so that they do not fall ill with diabetes. Individuals with a history of impaired glucose tolerance (IGT) or the pre-diabetic group need to adopt a healthy lifestyle by paying attention to food and drink intake, especially sweet foods and doing physical activity, so that it does not progress to diabetes mellitus. Objectives: To determine the effect of coconut sugar on blood sugar levels in prediabet sufferers in the Sleman Regency, Special Region of Yogyakarta. This research is focused on promotive and preventive efforts in efforts to prevent non-communicable diseases such as diabetes mellitus so as to achieve optimal levels of public health. Methods: This research was Quasy experimental research design, carried out by giving pre-diabetic sufferers 30 grams of coconut sugar a day for 2 weeks on selected respondents with blood sugar levels of 100 – 126 mg/dl. Respondents who met the criteria were then divided into 2 groups. The intervention group given 30 grams of coconut sugar per day for 2 weeks and the control group consume food and drinks as usual. Results: Based on comparative research of blood sugar levels before and after giving coconut sugar among prediabetes, the results showed that there was a significant decrease in blood sugar in the intervention group after giving with the level blood sugar average is 17.39 mg /dl and in the control group blood sugar level average is 6.83 mg/dl Conclusions: There is significant effect of coconut sugar to decrease level of blood sugar among prediabetes patients.